Incidence of Post-operative Pulmonary Complications Following Cytoreductive Surgeries and HIPEC: A Retrospective Analytic Study - Sureshan, Roopesh; B, Satheesan; Opneja, Sonali; C, Jashma; P, Joona; Divakaran, Namratha; John, Mayan (Asian Pacific Journal of Cancer Care, 2023)
Background and objective: Cytoreductive surgery (CRS) is performed to treat macroscopic disease, while Hyperthermic intraperitoneal chemotherapy (HIPEC) is used to address microscopic residual disease. Abdominal surgeries may be associated with pulmonary complications and prolonged hospital stays. This retrospective study aimed to determine the incidence of post-operative pulmonary complications occurring within 30 days following CRS and HIPEC, as well as identify the responsible risk factors. Materials and methods: The retrospective study included patients who underwent CRS and HIPEC. Patient data was retrieved from May 31, 2018, to June 30, 2022. Data was obtained from patient records and registers kept in the medical records library. Post-operative pulmonary complications were noted, and risk factors were identified. Results: A total of 27 CRS with HIPEC surgeries were performed during the study period. The procedures were conducted on patients with primary tumors of the ovary, colon, appendix, Ewing’s sarcoma pelvis, and peritoneum. Six patients developed post-operative pulmonary complications, including pleural effusion in four patients and acute respiratory distress syndrome (ARDS) in two patients. Conclusion: The incidence of post-operative pulmonary complications in our study following CRS and HIPEC was 22%. Pleural effusion was the most common complication observed, followed by ARDS. Intrinsic disease in association with hypoalbuminemia (< 2 gm/dl) was identified as an important factor contributing to pleural effusion.